CYP450 Genotype—Phenotype Concordance Using the Geneva Micrococktail in a Clinical Setting - Ing Lorenzini, Kuntheavy; Desmeules, Jules; Rollason, Victoria; Bertin, Stéphane; Besson, Marie; Daali, Youssef; Samer, Caroline F. (Frontiers in Pharmacology, 2021)
Pharmacokinetic variability is a major source of differences in drug response and can be due to genetic variants and/or drug-drug interactions. Cytochromes P450 are among the most studied enzymes from a pharmacokinetic point of view. Their activity can be measured by phenotyping, and/or predicted by genotyping. Depending on the presence of drugs and/or diseases that can affect their in vivo activity, both approaches can be complementary. In 2014, the Geneva cocktail using dried blood spots was validated in healthy volunteers for CYP450 phenotyping. Since its clinical implementation, it has been used in approximately 500 patients in various clinical situation. Our study aims to report the concordance between CYP450 genotype and phenotype in real-life patients. The prospectively collected data from patients who were genotyped and/or phenotyped between January 2014 and December 2020 were reviewed. A total of 537 patients were genotyped and/or phenotyped for CYP450 during this period, and 241 underwent simultaneous genotyping and phenotyping allowing for genotype/phenotype concordance assessment. Genotyping correctly predicted poor metabolizer phenotypes for most CYPs isoenzymes studied, whereas agreement was more variable for intermediate, normal, and ultrarapid metabolizers. Discrepancies between the phenotype predicted on the basis of genotyping and the measured phenotype were not always explained by concurrent medication (phenotypic switch). Therefore genotyping and phenotyping tests are complementary approaches when aiming to individualize drug therapy. In the 537 patients, the majority of clinical situations were observed with analgesic/anesthetic drugs (n=187), followed by antidepressants (n=153), antineoplastics (n=97), and immunosuppressants (n=93). Inefficacy (or low drug levels) and adverse drug reaction (or high drug levels) were the main reasons for testing. Genotype and/or phenotype results explained or at least contributed to the clinical event in 44% of cases.